Penggunaan Media Audio Visual untuk Meningkatkan Minat Belajar Peserta Didik - Siregar, Zainab; Mukhlis, Muhammad; Asnidar, Asnidar (Jurnal Kependidikan Profesi, 2024)
This study aims to explore the use of audio-visual media in increasing students' interest and motivation to learn. The type of research used is quantitative research with the method of classroom action research (PTK), where a group of learners is given learning materials using audio visual media, while the control group uses conventional methods. The audio-visual media used includes video, animation, images and sound, which are able to present the subject matter in a more interesting and interactive manner. By stimulating more senses, it facilitates better understanding and recall of information. The research also examines how variations in delivery methods can prevent boredom and meet the needs of different learning styles of learners. The integration of technology in the use of audio-visual media supports more flexible and adaptive learning, and enables more effective self-learning. The results showed that the use of audio-visual media significantly increased students' interest and motivation to learn compared to conventional methods. Learners who learn using audio-visual media are more focused, enthusiastic, and motivated to be actively involved in the learning process. Thus, it is important for educators to continue to develop and utilize audio visual media in the learning process to create a dynamic and optimal learning environment.